Enhancing 7 MW solar power plant performance in Thailand: Power management via energy time shift and voltage range control mode - Chattariya Sirisamphanwong; Karthikeyan Velmurugan; Narathip Manakul; Phairot Phanukan; Sirinuch Chindaruksa; Buntoon Wiengmoon; Kongrit Mansiri; Rattaporn Ngoenmeesri; Maruphong Konyu; Chatchai Sirisamphanwong (Ain Shams Engineering Journal)
In this study, to maintain the grid voltage within an allowable range, a fixed lagging 0.975 PF reactive power control without a Battery Energy Storage System (BESS) and energy time shift and voltage range control mode using BESS are performed independently. It was found that the reactive power control method effectively maintained the grid voltage within the allowable range, although it reduced the energy generation by 5670.8 MWh and 4505.8 MWh compared to the other two modes. The energy time shift mode met the grid load demand by 99.98 %, and voltage range control attained 68.75% grid load demand matching, but it maintained the grid voltage within an allowable range. On a technical performance basis, the energy time shift and voltage range control mode performed effectively; however, they increased the system’s payback period due to an additional investment cost for BESS.